Pergeseran Aksara dan Kebertahanan Bahasa Minangkabau dalam Tradisi Tafsir Ulama Minangkabau - Fithrah Lathifah; Ahmad Baidowi (Jalsah : The Journal of Al-quran and As-sunnah Studies, 2026)
This study explores the shift of script and the endurance of the Minangkabau language in the Qur’anic exegesis tradition of Minangkabau scholars during the twentieth century as a historical and cultural phenomenon. The transition from Jawi to Latin script represents not only a technical change in writing but also an epistemological transformation from the exclusive surau tradition to the modern madrasa and print-based public sphere. The study aims to explain the process of this script shift, the persistence of Minangkabau linguistic elements in Latin-script tafsir, and its implications for reading traditions, interpretation, and religious authority. Employing a qualitative, descriptive-historical approach through library research, the analysis focuses on five primary tafsirs: al-Burh?n, al-Qaul al-Bay?n, al-Da?wah wa al-Irsy?d, Tafsir Qur’an Karim, and Tafsir al-Azhar. Findings reveal that the Jawi script symbolized the scholarly authority of traditional ulama, while the Latin script expanded public accessibility and transformed intellectual authority into a more inclusive form. Despite the shift in medium, Minangkabau diction and idioms persisted as local expressions of Qur’anic understanding, maintaining the continuity of Islamic values within a cultural framework. In conclusion, Minangkabau Qur’anic exegesis reflects a dialogue between tradition and modernity, emphasizing language and script as markers of Islamic intellectual identity in the Indonesian archipelago.